Financial Technology Awareness Among Homestay Operators in Sarawak, Malaysia - Kartinah, Ayupp; Norizan, Jaafar; Michael, Tinggi (Human Resource Management Academic Research Society, 2021)
As a part of Malaysia’s tourism landscape, the homestay business has gone through various changes in the dynamic tourism industry. It was initially developed to allow tourists and visitors to experience the social and natural heritages of the local people as they live their daily life. Just like any other business, homestay business is also being impacted by the rapid development of information and communication technology (ICT) including the disruptive development of financial technology or better known as Fintech. This is widely acknowledged as an innovative solution for financial transactions due to the great convenience that it offers not only to the consumers but also the business operators. However, as the homestay business in Malaysia tends to be operated among micro, small and medium enterprises, or to be more precise are mainly operated as personal or family businesses, the adoption of Fintech services is still at the infant stage among homestay operators. Realizing the significance of Fintech towards the development of homestay business in Malaysia, a qualitative method was adopted involving in-depth interviews of 30 homestay operators. The site of the study is in Sarawak, which is the largest state in Malaysia. An open-ended, in-depth interview method is adopted as it enables the homestay operators to give their views in a robust and detailed manner. This study is needed to identify the cause of low adoption rate among homestay operators, hence, initiating the knowledge and later actions to encourage the homestay operators to reap the benefits that the Fintech has to offer